Photography as an Approach in Energy Transitions Research: Visual Surveying, Auto-Photography & Photo-Elicitation in Scotland’s Orkney Islands - Neil Gordon Davey (International Journal of Qualitative Methods)
Modern technology has significantly enhanced the accessibility of photography, broadening its use across various scientific disciplines. Digital cameras and smartphones have empowered researchers, especially in the field, to collect data more efficiently and intimately than many traditional methods allow. Photography’s longstanding relationship with social research has made it a crucial tool for co-creating knowledge and capturing data that non-visual approaches might overlook. Beyond mere illustration, photography contributes to a deeper understanding of complex contexts. However, despite its widespread application in the social sciences, there remains a notable gap in its use within energy transitions research in science and technology studies (STS). Drawing on personal experience in studying energy development in Scotland’s Orkney Islands, this article demonstrates how photography can enrich the research process. Although not without challenges, the article highlights approaches like visual surveying, auto-photography, and photo-elicitation. This illustrates the potential of photography, emphasizing its value as a research method to enhance understanding of the visual consequences of energy transitions in rural landscapes.